2015
DOI: 10.1002/ange.201411028
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a New Class of Tetracycline Lead Structures with Potent Antibacterial Activity through Biosynthetic Engineering

Abstract: Antimicrobial resistance and the shortage of novel antibiotics have led to an urgent need for new antibacterial drug leads. Several existing natural product scaffolds (including chelocardins) have not been developed because their suboptimal pharmacological properties could not be addressed at the time. It is demonstrated here that reviving such compounds through the application of biosynthetic engineering can deliver novel drug candidates. Through a rational approach, the carboxamido moiety of tetracyclines (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The next steps are cyclization and aromatization of the CHD backbone, likely carried out by a number of proteins. The final step involves modifications to the core, including C‐9 methylation and a C‐4 hydroxylation . The chd cluster contains a number of features related to the classification of CHD as atypical: an additional gene for a putative two‐component cyclase/aromatase that might be responsible for the unique aromatization pattern, a gene for a putative aminotransferase for C‐4 (opposite stereochemistry to that of TCs), and a gene for a putative C‐9 methylase, a unique feature of this biosynthetic cluster.…”
Section: Polyketides Biosynthesis In Amycolatopsismentioning
confidence: 99%
“…The next steps are cyclization and aromatization of the CHD backbone, likely carried out by a number of proteins. The final step involves modifications to the core, including C‐9 methylation and a C‐4 hydroxylation . The chd cluster contains a number of features related to the classification of CHD as atypical: an additional gene for a putative two‐component cyclase/aromatase that might be responsible for the unique aromatization pattern, a gene for a putative aminotransferase for C‐4 (opposite stereochemistry to that of TCs), and a gene for a putative C‐9 methylase, a unique feature of this biosynthetic cluster.…”
Section: Polyketides Biosynthesis In Amycolatopsismentioning
confidence: 99%
“…Remarkably, they also differ in their mechanism of action which is believed to involve interference with the bacterial membrane and disruption of its function . CHD is produced by a rare actinomycete strain Amycolatopsis sulphurea NRRL 2822 and displays potent broad‐spectrum antibacterial activity . CHD has been shown to be highly active against Gram‐positive and some Gram‐negative pathogens including Staphylococcus aureus strains and shows potent activity against multi‐resistant pathogens .…”
mentioning
confidence: 99%
“…CHD is produced by a rare actinomycete strain Amycolatopsis sulphurea NRRL 2822 and displays potent broad‐spectrum antibacterial activity . CHD has been shown to be highly active against Gram‐positive and some Gram‐negative pathogens including Staphylococcus aureus strains and shows potent activity against multi‐resistant pathogens . Although its chemical structure resembles that of typical TCs it has been demonstrated that CHD is likely not a translation inhibitor .…”
mentioning
confidence: 99%
See 2 more Smart Citations